14C selective extraction from French graphite nuclear waste by CO2 gasification. (May 2018) - Pageot, J.; Rouzaud, J.-N.; Gosmain, L.; Duhart-Barone, A.; Comte, J.; Deldicque, D.
Abstract: The decommissioning of French gas-cooled nuclear reactors, all stopped since 1994, will generate 23, 000 tons of nuclear waste containing 14 C among other radionuclides. This work aims at presenting and testing a selective extraction treatment of this radionuclide from graphite waste by carbon dioxide gasification. In previous works, we highlighted that graphite turns into a heterogeneously degraded carbon with neutron irradiation and 14 C could preferentially be concentrated in the most degraded zones. Moreover, these last react selectively with CO2 that would allow the 14 C extraction from graphite waste. The results on graphite waste are promising with the quarter of 14 C inventory extracted for a relative weight loss of few percent. Up to 68% of 14 C inventory was extracted, but with a more important mass consumption. Thus, the potential of this selective 14 C extraction would allow imagining alternative scenarios for graphite waste management. Highlights: Graphite waste potentially will represent 23000 tons of nuclear waste in France, and 250000 tons worldwide. This graphite waste treatment aim is to selective extract the 14 C from the most degraded areas of the material. The quarter of 14 C inventory is extracted for a weight loss of only few percent. With optimizations, this treatment could allow helping the graphite waste management.